2023
DOI: 10.3390/antiox13010018
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defence in Labeo rohita to Biotic and Abiotic Stress: Insight from mRNA Expression, Molecular Characterization and Recombinant Protein-Based ELISA of Catalase, Glutathione Peroxidase, CuZn Superoxide Dismutase, and Glutathione S-Transferase

Sonali Parida,
Pramoda Kumar Sahoo

Abstract: Fish possess numerous enzymatic antioxidant systems as part of their innate immunity. These systems have been poorly studied in Labeo rohita (rohu). The present study characterized and investigated the role of antioxidant genes in the defence mechanisms against two types of stressors, including infection and ammonia stress. Four key genes associated with antioxidant activity–catalase, glutathione peroxidase, glutathione S-transferase, and CuZn superoxide dismutase were successfully cloned and sequenced. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…Neurons and glial cells in the CNS, including the spinal cord, are particularly susceptible to oxidative and electrophilic stress due to their high polyunsaturated fatty acid content, high oxidative metabolic activity, and strong production of reactive oxygen metabolites and relatively low antioxidant capacity ( Parida and Sahoo, 2023 ). Studies have shown that the presence of oxidative stress has the potential to exacerbate neuroinflammation and promote apoptotic processes.…”
Section: Pathophysiological Process Of Scimentioning
confidence: 99%
“…Neurons and glial cells in the CNS, including the spinal cord, are particularly susceptible to oxidative and electrophilic stress due to their high polyunsaturated fatty acid content, high oxidative metabolic activity, and strong production of reactive oxygen metabolites and relatively low antioxidant capacity ( Parida and Sahoo, 2023 ). Studies have shown that the presence of oxidative stress has the potential to exacerbate neuroinflammation and promote apoptotic processes.…”
Section: Pathophysiological Process Of Scimentioning
confidence: 99%